Al-Munāfarah's skills and it impact on the development of Arabic rhetorical thought - Ayman Khamis Abdullatif Abu Mustaffa (Departement of Arabic Language and Literature, IAIN Syekh Nurjati Cirebon, 2021)
This study is concerned with standing on the bragging about our Arab heritage, an attempt to elucidate the impact of this art on the development of Arab rhetorical thought, as the brags can be an early start for the pilgrims' theory that came as the result of the effects of modern stylistic studies. The study tries to root and clarify this through heritage books, and this is not what makes us stand as the defender of heritage, but rather it is an attempt to link the old with the modern, as ancient Arab literature was not separate from life, but rather discussed life issues in a literary manner. Also, in this type of art, we notice the availability of dramatic elements that can be indicative of theatrical art for Arabs, so bragging is not just a speech, but rather a recitation, movement and interaction with the audience.تهتم هذه الدراسة بالوقوف على المفاخرة في تراثنا العربي، محاولة استجلاء أثر هذا الفن في تطور التفكير البلاغي العربي، فالمفاخرات يمكن أن تكون بداية مبكرة لنظرية الحجاج التي جاءت أثرا من آثار الدراسات الأسلوبية الحديثة. والدراسة تحاول تأصيل ذلك وتوضيحه من خلال كتب التراث، وليس في ذلك ما يجعلنا نقف موقف المدافع عن التراث، ولكن هي محاولة للربط بين القديم والحديث، فالأدب العربي القديم لم يكن منفصلا عن الحياة، بل كان يناقش قضايا الحياة بأسلوب أدبي. كما أننا في هذا النوع من الفن نلحظ توافر العناصر الدرامية التي يمكن أن تكون مؤشرا للفن المسرحي عند العرب، فليست المفاخرة مجرد خطاب، بل هي إلقاء وحركة وتفاعل مع الجمهور.